The association of perceptions of harmfulness and addictiveness on the age of initiation of cigar product use among youth: Findings from the Population Assessment of Tobacco and Health (PATH) study, 2013–2017 - Chen, Baojiang; Spells, Charles E.; Bluestein, Meagan A.; Kuk, Arnold E.; Harrell, Melissa B.; Pérez, Adriana (Frontiers in Public Health, 2022)
Background Perceptions of cigar products’ harmfulness and addictiveness in youth are associated with subsequent cigar product initiation, but their association on the age of initiation of cigar product use is unknown. Methods The association of perceptions of harmfulness and addictiveness at youth’s first wave of PATH participation (waves 1 or 2 in years 2013-2015) on the age of initiation of (i) ever, (ii) past 30-day, and (iii) fairly regular use of any cigar products (cigarillos, filtered cigars, or traditional cigars) during the followed-up in PATH waves 2-4 (2014-2017) was estimated using weighted interval-censored Cox proportional hazards models. Also, the association of the interaction between perceptions of harmfulness and addictiveness and the age of initiation of any cigar use are reported. Hazard ratios (HR) and 95% confidence intervals(CI) are reported. Results Among youth who had ever heard of cigar products, youth who perceived cigars to be “low-medium harmfulness and low-medium addictiveness” had 60% (HR: 1.60, 95%CI: 1.36-1.89) higher hazard risk to initiate ever cigar product use at an earlier age, and had 46% (HR:1.46, 95%CI: 1.14-1.86) higher hazard risk to initiate past 30-day cigar product use at younger ages than those who perceived cigars to be “high harmfulness and high addictiveness”. Moreover, youth who perceived cigars to be “low-medium harmfulness and high addictiveness” had 33% (HR:1.33, 95%CI: 1.15-1.53) higher hazard risk to initiate ever cigar product use at younger ages than those who perceived cigars to be “high harmfulness and high addictiveness”. Youth who reported “high harmfulness and low-medium addictiveness” (HR: 0.24, 95% CI: 0.07-0.83) had 76% lower hazard risk to initiate fairly regular use of cigar products at younger ages compared to youth who reported “high harmfulness and high addictiveness”. Conclusions Prevention and awareness campaigns should reinforce the unique potential for harm and addiction of cigar products to curb cigar product initiation among US youth.